The preeminence of ethnic diversity in scientific collaboration - Bedoor K. AlShebli (Nature Portfolio, 2018)
Diversity is believed to raise effectiveness and performance but it contains many aspects. Here the authors studied the relationship between research impact and five classes of diversity and found that ethnic diversity had the strongest correlation with scientific impact.